Теорія ризиків інформаційної безпеки в WordPress - Кутя, Б. С. (ХНУРЕ, 2024)
Information security risk theory is a key aspect in managing the security of WordPress websites. This abstract explores the theoretical framework of risk management in the context of WordPress, one of the most widely used content management systems worldwide. The abstract highlights key risk factors such as vulnerabilities in WordPress core software, themes, and plugins. In addition, it discusses strategies to prevent and mitigate risks, including regular software updates, strong password policies, and implementing security plugins like Wordfence. By understanding and effectively applying information security risk theory, WordPress site owners and administrators can increase the resilience and integrity of their online platforms in the face of emerging cybersecurity challenges.
Keywords: WordPress; інформаційна безпека